Australian higher education institutions transforming the future of teaching and learning through 3D virtual worlds - Gregory, S.; Gregory, B.; Campbell, M.; Farley, H.; Sinnappan, S.; Kennedy-Clark, S.; Craven, D.; Murdoch, D.; Lee, M.; Wood, D.; Grenfell, J.; Thomas, A.; et al. (The University of Queensland, 2010)
What are educators' motivations for using virtual worlds with their students? Are they using them to support the teaching of professions and if this is the case, do they introduce virtual worlds into the curriculum to develop and/or expand students' professional learning networks? Are they using virtual worlds to transform their teaching and learning? In recognition of the exciting opportunities that virtual worlds present for higher education, the DEHub Virtual Worlds Working Group was formed. It is made up of Australian university academics who are investigating the role that virtual worlds will play in the future of education and actively implementing the technology within their own teaching practice and curricula. This paper presents a typology for teaching and learning in 3D virtual worlds and applies the typology to a series of case studies based on the ways in which academics and their institutions are exploiting the power of virtual worlds for diverse purposes ranging from business scenarios and virtual excursions to role-play, experimentation and language development. The case studies offer insight into the ways in which institutions are transforming their teaching for an unknown future through innovative teaching and learning in virtual worlds. The paper demonstrates how virtual worlds enable low cost alternatives to existing pedagogies as well as creating opportunities for rich, immersive and authentic activities that would otherwise not be feasible or maybe not even be possible. Through the use of virtual worlds, teaching and learning can be transformed to cater for an unknown future.